SINTESIS SURFAKTAN TURUNAN AMIDA YANG DIPEROLEH DARI REKASI METIL RISINOLEAT DAN ETILENDIAMINA - Daniel Tarigan; Magdaleni Rahayu Agustina; Soerja Kosenarpadi (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2018)
Interesterification of castor oil with methanol using base catalyst gave mixture of fatty acid methyl esther (FAME) castor oil. Methyl risinoleate as major composition of methyl esther castor oil was subjected to column chromatography using petroleum ether:diethyl ether (19:1, v/v) as eluent, to give yield 73%. Amidation of methyl risinoleate with ethylendiamine under refluks condition using benzene as solvent for ± 12 hours and catalyst NaOCH3, gave 1,3–Dirisinoleil-Etilendiamida compound and 59% yield. The reactioned product 1,3–Dirisinoleil-Etilendiamida has been confirmed its structure using FT-IR spectroscopy, and Hidrofile Lipofile Balance (HLB) value was determined by titration method 12,56